Strategi Kebijakan Peningkatan Kualitas Hidup Lanjut Usia Melalui Perlindungan Sosial Sepanjang Hayat - Sari, Ria Permana (Syntax Corporation, 2025)
Since 2021, Indonesia has undergone a significant demographic transition, moving towards an ageing population structure with a percentage of the elderly population of 10%. In 2045, it is expected that there will be an explosion of the elderly with a proportion of the elderly population of 20.31%. The increasing number of elderly people is a tan. This can be seen from the large number of poor elderly, the uneven health services that can be accessed by the elderly, and the small proportion of the elderly who have old-age/retirement guarantees. This paper aims to compile policy recommendations that can be implemented by the government and related stakeholders to support the improvement of the social welfare of the elderly, namely through the strengthening of the social protection system, so that it can support the improvement of the dignity, independence and social welfare of the elderly as a whole. One of the alternative policies that can be taken in the implementation of social protection to support active ageing, is the development of community-based elderly care services, so that it can provide services that are easily accessible to the elderly according to their needs.